Accounting for decision making and control - Zimmerman, Jerold L. 1947- (McGraw-Hill Irwin, 2009)
Summary: This book demonstrates that managerial accounting is an integral part of the firm's organizational architecture, not just an isolated set of computational topics. Managers in all organizations, throughout their professional careers, interact with their accounting systems as it is both a source of information for decision making and part of the organization's control mechanisms.